Design and Control of a Powered Lower Limb Orthosis Using a Cable-Differential Mechanism, COWALK-Mobile 2 - Park, Jaehwan; Park, Seunghan; Kim, Chankyu; Park, Jong Hyeon; Choi, Junho (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
Powered lower limb orthoses have been commercially available for patients with Spinal Cord Injuries (SCI) or stroke. However, studies have shown that there are adverse effects on kinematics as well as metabolic energy of the users due to the additional mass of the orthoses to the lower limbs. Since additional metabolic energy required to use the powered orthoses is one of the reasons to avoid using them, it is important to reduce the mass and moment of inertia of the exoskeletons for longer use and better outcomes. In this study, a powered-lower-limb orthosis for stroke patients using a cable-differential mechanism, which is called COWALK-Mobile 2, was proposed. The cable-differential mechanism was utilized to transmit the actuating torques from actuators to the hip and knee joints. The cable-differential mechanism enabled the actuators to be located near the hip, which yields reduced inertia of the device, as well as the loads at the joints to be shared by the actuators, which results in smaller required actuator torque. Optimal radii of the pulleys for the cable-differential mechanism were found for efficient load-sharing during walking. Experimental results with a healthy person walking on a level surface have shown that larger joint torques were generated with smaller actuator torques.
Keywords: SOFT EXOSUIT; ASSISTANCE; WALKING